Explicating concepts in reasoning from function to form by two-step innovative abductions. Issue 2 (18th April 2016) - Kroll, Ehud; Koskela, Lauri
Abstract: The mechanism of design reasoning from function to form is suggested to consist of a two-step inference of the innovative abduction type. First is an inference from a desired functional aspect to an idea, concept, or solution principle to satisfy the function. This is followed by a second innovative abduction, from the latest concept to form, structure, or mechanism. The intermediate entity in the logical reasoning, the concept, is thus made explicit, which is significant in following and understanding a specific design process, for educating designers, and to build a logic-based computational model of design. The idea of a two-step abductive reasoning process is developed from the critical examination of several propositions made by others. We use the notion of innovative abduction in design, as opposed to such abduction where the question is about selecting among known alternatives, and we adopt a previously proposed two-step process of abductive reasoning. However, our model is different in that the two abductions used follow the syllogistic pattern of innovative abduction. In addition to using a schematic example from the literature to demonstrate our derivation, we apply the model to an existing, empirically derived method of conceptual design called "parameter analysis" and use two examples of real design processes. The two synthetic steps of the method are shown to follow the proposed double innovative abduction scheme, and the design processes are presented as sequences of double abductions from function to concept and from concept to form, with a subsequent deductive evaluation step.